Students' Perceptions on the Use of E-Portfolio for Learning Assessment - Chalim Fathul Muin; Hafidah Hafidah; Amira Muflicha Daraini (STAI Hubbulwathan Duri, 2021)
This study aims at probing students' perceptions of utilizing e-portfolio for learning at the university. The study was qualitatively conducted as a case study. The subjects were 16 undergraduate students of the seventh semester in a university. The data were obtained by conducting interviews and disseminating a questionnaire. The results of the study revealed that most participants demonstrated positive views towards the use of e-portfolio. Further, the participants acknowledged some crucial benefits of utilizing the e-portfolio. They were extended to; increasing the motivational beliefs and self-efficacy, learning new things, accomplishing the English tasks effectively, giving beneficial effects for the learning, and improving students' ability in English. The findings are expected to bring light to stakeholders to consider e-portfolio to encourage students' learning enthusiasm and engagement.